Short-term follow-up of disc cell therapy in a porcine nucleotomy model with an albumin-hyaluronan hydrogel: in vivo and in vitro results of metabolic disc cell activity and implant distribution - Omlor, Georg; Fischer, Jennifer; Kleinschmidt, Kerstin; Benz, K.; Holschbach, Jeannine; Brohm, Kathrin; Anton, M.; Gühring, Thorsten; Richter, Wiltrud (European spine journal, 2014)
Cell therapy would be favorably performed immediately after nucleotomy, to restore intervertebral disc functionality and to slow down disc degeneration. Promising results were reported from small animal models but remaining problems, especially in larger animals, include loss of vital cells due to annular damage at the injection site and detrimental intradiscal conditions. The aim of the present study was to optimize cell-based disc therapy using a new albumin-hyaluronan hydrogel together with bone marrow-derived mesenchymal stem cells in a large porcine disc model.